1996
DOI: 10.1056/nejm199605023341802
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Combination of Beta Carotene and Vitamin A on Lung Cancer and Cardiovascular Disease

Abstract: After an average of four years of supplementation, the combination of beta carotene and vitamin A had no benefit and may have had an adverse effect on the incidence of lung cancer and on the risk of death from lung cancer, cardiovascular disease, and any cause in smokers and workers exposed to asbestos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
1,511
10
53

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 3,234 publications
(1,642 citation statements)
references
References 23 publications
42
1,511
10
53
Order By: Relevance
“…A bene®cial effect of high dietary consumption of fresh fruits and vegetables, the main source of antioxidants, was repeatedly shown in epidemiological studies (Rimm et al, 1996;Key et al, 1996;Ness & Powles, 1997). This explanation would also accommodate the results of the recent clinical trials which failed to show any bene®cial effects of beta-carotene supplementation on the occurrence of CVD (The Alpha-Tocopherol, BetaCarotene Cancer Prevention Study Group, 1994;Hennekens et al, 1996;Omenn et al, 1996).…”
Section: Discussionmentioning
confidence: 89%
“…A bene®cial effect of high dietary consumption of fresh fruits and vegetables, the main source of antioxidants, was repeatedly shown in epidemiological studies (Rimm et al, 1996;Key et al, 1996;Ness & Powles, 1997). This explanation would also accommodate the results of the recent clinical trials which failed to show any bene®cial effects of beta-carotene supplementation on the occurrence of CVD (The Alpha-Tocopherol, BetaCarotene Cancer Prevention Study Group, 1994;Hennekens et al, 1996;Omenn et al, 1996).…”
Section: Discussionmentioning
confidence: 89%
“…Plasma levels of the carotenoids including lutein, a-cryptoxanthin, lycopene, a-carotene and b-carotene were all higher in the vegetarian group by about 15% on average, and this is consistent with the greater intake of vegetables and subsequently a higher intake of carotenes in vegetarians. These carotenoids have been found to exhibit anti-carcinogenic and anti-atherogenic properties as reviewed previously (Mayne, 1996;Palace et al, 1999), although it should be noted that randomized intervention trials with relatively high doses of individual carotenoids fed in isolation have shown an increased risk of some chronic diseases (Alpha-Tocopherol, Beta Carotene Cancer Prevention Study Group, 1994;Omenn et al, 1996). Nonetheless, the combined effects of increased levels of various carotenoids could have significant biological effects, as it has been suggested that several phytochemicals in combination may have a better protective effect than their individual parts (Liu, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In ecological studies and early case-control studies it appeared that β-carotene was a cancer-protective agent. Randomized controlled trials of β-carotene found that the isolated nutrient was either neutral [141] or actually increased risk of lung cancer in smokers [142,143]. Beta-carotene may be a marker for intake of fruits and vegetables, but it does not have a powerful protective effect in isolated pharmacological doses.…”
Section: Reviewmentioning
confidence: 99%